Synthesis of Silver Nanoparticles by Chemical Reduction Method and a Comparison Study of Silver-filled Epoxy Thin Film Composites - Suriati, Ghazali; Mariatti, Jaafar; Azizan, Aziz (2013)
Uniform, well-dispersed, silver nanoparticles (AgNPs) were prepared by a simple chemical reduction method. The particles were synthesized via the reduction of AgNO 3 by trisodium citrate and ascorbic acid as a surfactant. The resulting AgNP5 were characterized by x-ray diffraction analysis (XRD), transmission electron microscopy (TEM), and scanning electron microscopy (SEM). It was found that the size of the AgNP5 ranged from 35-80 nrn, with an average of 50 rim. The as-synthesized AgNPs were then dispersed into an epoxy matrix, to form electrically conductive adhesives (ECA5), in the form of a thin film. For comparison, ECAs produced using commercial silver particles, e.g. silver flakes and silver nanoparticles, were prepared at a constant filler loading, and the electrical conductivity was observed. It was found that the as-synthesized AgNPs showed the highest electrical conductivity (2.53x10 1 S/cm) in comparison to the ECAs prepared using commercial particles.